Cultural tourism products mapping using geographic information systems in Bekasi - Vitha Octavanny; Kenyo Kharisma Kurniasari (Universitas Merdeka Malang, 2022)
This study aims to identify and analyze the main destinations for cultural tourism in Bekasi City Regency using the Geographic Information System by using mixed methods through spatial geography and a descriptive qualitative approach. The data collection methods are through field surveys with notes, interviews, and documentation. The ArcGIS 10 software is used in order to visualize the data. Furthermore, the qualitative description of the data was served by using the theory of Tourism Products (Attraction, Accessibility, Amenities, and Ancillary). The results of the study indicate that there are four cultural tourism destinations that are the potential to become the representatives of cultural tourism in Bekasi, namely Kranggan Traditional Village, Juang 45 Museum, Hok Lay Temple, and Saung Ranggon Cultural Heritage. The data on each destination is presented in both visual and descriptive form with the purpose to know the distribution of the mapping pattern for the tourism-producing supporting facilities at the attraction and can then be used as an of providing information, data updates, and references to accommodate the developments and policies around the area in order to improve the quality of the tourist experiences while visiting.